Auditoría tributaria en las empresas exportadoras PYMES para optimizar la devolución del Impuesto al Valor Agregado - Ramírez Jácome, Karen Elizabeth (2021)
The research project analyzes the Tax Audit in SME exporting companies to optimize the return of the Value Added Tax, and its purpose is to contribute to the use of the tax incentives established by the Tax Administration that will allow facing complications in the financing that is a significant limiting factor to carry out its operations. SMEs in Ecuador have flexibility to adapt to changes of a social type or job creation; but sometimes there are conditions to the role they play due to the factor they have generated in the productive environment; fiscal powers and exports, however its activities energize the country's economy. Chapter I presents the approach to the problem of VAT refund in Exporting SMEs, and also justification, general objective and specific objectives established regarding the research topic.......